Political polarisation in Slovenia and its effects on liberal democracy - Malčič, Matevž (Teorija in praksa, 2023)
Concerns have been raised over the possible link between the growing political polarisation and fears of autocratisation in Slovenia. Faced with a lack of empirical data, we seek to answer two questions. First, how has political polarisation developed in Slovenia? We show that Slovenia has experienced massive increases in both ideological and affective polarisation on the levels of the citizenry and political parties. Second, what has been the effect of political polarisation on liberal democracy in Slovenia? A GLS (generalised least squares) model for the period 1992 to 2022 confirms negative effects only for affective, but not ideological polarisation regarding V-Dem’s liberal democracy and judicial constraints on the executive indice
Keywords: affective polarisation; autocratisation; avtokratizacija; čustvena polarizacija; ideological polarisation; ideološka polarizacija; political polarisation; politična polarizacija; Politične stranke; Politika in vladanje; SJM; Slovenian publiblic opinion; Slovensko javno mnenje